Role of healthcare professionals in drug-drug interactions and clinical interventions - Siddiqui, Durr-e-Shahwar (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Healthcare professionals including prescribers, pharmacists and nurses must have adequate knowledge of drug-drug interactions because they can cause toxicity, loss of efficacy, and side effects. This study was aimed to assess the respective roles of healthcare professionals in preventing drug-drug interactions by clinical interventions. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This study was conducted at a Secondary Care Hospital of Pakistan in which total 1000 prescriptions were assessed for drug-drug interactions. Questionnaires and descriptive statistics were tools to assess the satisfaction of prescribers with pharmacists and their own prescribed medications before and after the clinical interventions. Modifications in medication therapies were done accordingly after the evaluation and acceptance of interventions. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The p-value was highly significant (p<0.05) which showed that the collaboration between healthcare professionals is necessary to avoid drug-drug interaction by clinical interventions. Acceptance rate of interventions was 77%. Clinical interventions are a useful tool in minimizing and preventing drug-drug interactions. The compliance of prescribers with their own prescribed medication regimens increased after clinical interventions. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Prescribers, pharmacists and nurses have their respective roles in preventing drug-drug interactions and they must review the appropriateness of every medication order for clinical interventions.